PAP smear in pregnancy: a hospital-based study - Priya, S. Senthil; Shankar, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pregnant and non-pregnant women are at similar risk for CIN and cervical cancer. The incidence of abnormal cervical cytologic findings during pregnancy is 0.72 to 1.67%. Approximately 86% of all squamous intraepithelial lesions (SIL) indentified during pregnancy are classified as low-grade SIL, whereas 14% are high- grade SIL. The aim of this study is to assess the incidence of Pap smear abnormalities among antenatal woman presenting to present hospital. Methods: A prospective study was conducted in present medical college hospital in the department of Obstetrics and Gynecology for a period of one year from Jan 2017 to Dec 2017. A total of 200 antenatal women were included in the study. Ayre’s spatula was used to conduct smear tests in this study. All smears were immediately sprayed with a fixative and sent to the department of Pathology. The cytological results were reported based on the Bethesda classification system 2001. Results: The pap smear report revealed that 26% of the subjects had inflammatory changes and for 66% it showed negative for intraepithelial lesion and for only 1% of the subjects had signs related to carcinoma cervix in which one patient had Atypical Squamous Cell of Undetermined Significance (ASCUS) and another patient had Low-grade Squamous Intraepithelial Lesion (LSIL) and no satisfactory sample was able to be obtained in 6% of the subjects. In present study authors found a statistically significant association between the age at marriage and the pap smear report, lower the age at marriage (<20 years) higher the incidence of inflammatory changes in the cervix and both the patients who were reported with ASCUS and LSIL were in the age of 15 and 16 years respectively. Conclusions: Clinicians should make every effort to educate, counsel and screen pregnant women if they have not had a Pap test in the past.